MAJOR DEPRESSION AMONG PREGNANT MOTHERS WITH HIV: CORRELATES AND SUGGESTED INTERVENTIONS (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2017)
Introduction: Psychological disturbance particularly depression is common among people living with HIV infection. More so among pregnant mothers due to concerns with regard to safe delivery, transmission of HIV infection to child, worries about the future and so on. Therefore, this study was undertaken to explore and describe the prevalence and correlates of depression in order to plan an appropriate intervention to ensure quality of life to women with HIV and their children.Methodology: Antenatal mothers with HIV infection who attended Department of Obstetrics and Gynecology, Government Rajaji Hospital, Madurai between December 2007 and September 2008 for parturition were included in the study. Depression was assessed using the center for epidemiology studies depression scale (CES-D). The scale has 20 items, with a 4 point Likert scale scores ranging from 0-3 for each statement.Results: A total of 53 respondents were included in the study. Median age of the respondents was 25 years. Despite availability of services of Voluntary Counselling and Testing Centre (VCTC) only 34 respondents underwent HIV screening Depression score. One tenth of them have experienced major depression. Sixteen respondents were depressed on knowing their HIV status, 22 respondents were shocked on receiving of positive results while six respondents attempted to commit suicide. Feeling of discrimination (p-0.003) and thought of abortion after knowing the HIV positive status (p-.003) had significant influence in experience of major depression.Conclusion: Quality of services of counsellors at antenatal clinics need to be improved and encouraged to periodically assess the psychological needs of antenatal / pregnant mothers. Sensitizing women on methods of family planning should begin during pregnancy and in the post natal period. Referral services should be strengthened further for timely intervention.SAARC J TUBER LUNG DIS HIV/AIDS, 2017; XIV(1), Page: 40-45